A Phylogenomic Framework and Divergence History of Cephalochordata Amphioxus - Zhang, Qi-Lin; Zhang, Guan-Ling; Yuan, Ming-Long; Dong, Zhi-Xiang; Li, Hong-Wei; Guo, Jun; Wang, Feng; Deng, Xian-Yu; Chen, Jun-Yuan; Lin, Lian-Bing (Frontiers in Physiology, 2018)
Amphioxus, or cephalochordates, are often used as the living invertebrate proxy of vertebrate ancestors and are widely used as evolutionary biology models of chordates. However, their phylogeny, divergence history, and speciation characteristics remain poorly understood, and phylogenomic studies to explore these problems lacking entirely from the literature. Here, we determined a new transcriptome of Branchiostoma japonicum. Combined with mass sequences of all other 18 species, a 19-way phylogeny was constructed via multiple methods (ML, BI, PhyloBayes, and ASTRAL), consistently supporting a phylogeny of [(B. belcheri + B. japonicum) + (B. lanceolatum + B. floridae) + Asymmetron lucayanum] in amphioxus. Congruent phylogenetic signals were found across mitochondrial genes, 12S RNA, and complete mitochondrial genomes according to previous reports, indicating that 12S RNA may have potential as a molecular marker for phylogenetic analysis in amphioxus. Molecular dating analysis indicated a radiation of the cephalochordates during the Cretaceous (∼104-61 million years ago), supporting an association between the diversification and speciation of cephalochordates with continental drift and associated changes in their respective habitats during this time. The identified functional enrichment analysis for species-specific domains indicated that their function mainly involves immune response, apoptosis, and lipid metabolism and utilization, signaling that pathogens and changes of energy requirements are an important driving force for amphioxus speciation. This study represents the first large-scale phylogenomic analysis of most major amphioxus genera based on phylogenomic data, providing a new perspective on both phylogeny and divergence speciation of cephalochordates.